Proceedings IEEE 24th Annual Joint Conference of the IEEE Computer and Communications Societies.
DOI: 10.1109/infcom.2005.1497917
|View full text |Cite
|
Sign up to set email alerts
|

Coverage and connectivity of ad hoc networks in presence of channel randomness

Abstract: Abstract-In this paper, we present an analytical procedure for the computation of the node isolation probability in an ad hoc network in the presence of channel randomness, with applications to shadowing and fading phenomena. Such a probability coincides with the complement of the coverage probability, given that nodes are distributed according to a Poisson point process. These results are used to obtain an estimate of the connectivity features for very dense networks. For the case of superimposed lognormal sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
113
0
1

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(121 citation statements)
references
References 40 publications
7
113
0
1
Order By: Relevance
“…A distance-power model cannot readily account for shadow fading since signal strength at the receiver is determined more by the presence of an obstacle blocking the path to the transmitter than by distance. In addition, recent investigations show that the connectivity of ad hoc networks with channel 0018-9448/$20.00 © 2006 IEEE randomness, such as that caused by shadow fading, is similar to the connectivity in a random graph [24]. Some models that consider channel randomness are studied in [25], [26], where it is shown that the resulting random network has some realistic connectivity properties lacking in a purely deterministic model.…”
Section: Introductionmentioning
confidence: 99%
“…A distance-power model cannot readily account for shadow fading since signal strength at the receiver is determined more by the presence of an obstacle blocking the path to the transmitter than by distance. In addition, recent investigations show that the connectivity of ad hoc networks with channel 0018-9448/$20.00 © 2006 IEEE randomness, such as that caused by shadow fading, is similar to the connectivity in a random graph [24]. Some models that consider channel randomness are studied in [25], [26], where it is shown that the resulting random network has some realistic connectivity properties lacking in a purely deterministic model.…”
Section: Introductionmentioning
confidence: 99%
“…According to [31][32][33], the corresponding CDF and expectations of the radio range for the above fading models are as follows.…”
Section: Theorem 19 the Connectivity For The Random Radio Range Casementioning
confidence: 99%
“…with zero mean, variance σ 2 , which represents the channel fluctuations. This channel model was also adopted by Orriss and Barton Orriss & Barton (2003) and other Authors Miorandi & Altman (2005 …”
Section: Link and Connectivity Modelsmentioning
confidence: 99%